VARIATIONALLY-BASED EFFECTIVE DYNAMIC THICKNESS FOR LAMINATED GLASS BEAMS - Jaroslav Schmidt; Alena Zemanová; Tomáš Janda; Jan Zeman; Michal Šejnoha (Acta Polytechnica CTU Proceedings)
Laminated glass, consisting of glass layers connected with transparent foils, has found its applications in civil, automotive, or marine engineering. Due to a high contrast in layer properties, mechanical response of laminated glass structures cannot be predicted using classical laminate theories. On the other hand, engineering applications demand easy-to-use formulas of acceptable accuracy. This contribution addresses such simplified models for free vibrations of laminated glass beams, with the goal to determine their natural frequencies and modal damping properties. Our strategy is to approximate the complex behavior of a laminated structure with that of an equivalent monolithic beam. Its effective thickness is determined by the variational method proposed by Galuppi and Royer-Carfagni for static problems, which we extended for modal analysis. We show that this new approach overcomes inaccuracies of the currently used dynamic effective thickness model by López-Aenlle and Pelayo.